EFFECTS OF TEMPERATURE AND PRESSURE TIME IN THE MANUFACTURE OF PARTICLEBOARDS - Iwakiri, Setsuo; Trianoski, Rosilani; Rosa, Thiago Souza; Silva da Costa, Leandro Sousa (Floresta, 2019)
The objective of this work was to evaluate the effects of three different temperatures and pressing times, near of industrial conditions, on the properties of experimental panels produced in the laboratory. The objective of this work was to evaluate the effects of three different temperatures and pressing times, near of industrial conditions, on the properties of experimental panels produced in the laboratory. The objective of this work was to evaluate the effects of three different temperatures and pressing times, near of industrial conditions, on the properties of experimental panels produced in the laboratory. The increase in the pressing time did not significantly affect the physical properties of the panels but improved their mechanical properties. The increase in the pressing temperature reduced the mechanical properties of the panels.